Brief report: miR‐290–295 regulate embryonic stem cell differentiation propensities by repressing pax6. (28th October 2013) - Kaspi, Haggai; Chapnik, Elik; Levy, Maayan; Beck, Gilad; Hornstein, Eran; Soen, Yoav
Abstract: microRNAs of the miR‐290–295 family are selectively expressed at high levels in mouse embryonic stem cells (mESCs) and have established roles in regulating self‐renewal. However, the potential influence of these microRNAs on cell fate acquisition during differentiation has been overlooked. Here, we show that miR‐290–295 regulate the propensity of mESCs to acquire specific fates. We generated a new miR‐290–295‐null mESC model, which exhibits increased propensity to generate ectoderm, at the expense of endoderm and mesoderm lineages. We further found that in wild‐type cells, miR‐290–295 repress Pax6 and ectoderm differentiation; accordingly, Pax6 knockdown partially rescues the mESCs differentiation impairment that is caused by loss of miR‐290–295. Thus, in addition to regulating self‐renewal, the large reservoir of miR‐290–295 in undifferentiated mESCs fine‐tunes the expression of master transcriptional factors, such as Pax6, thereby regulating the equilibrium of fate acquisition by mESC descendants. Stem Cells 2013;31:2266–2272